2018
DOI: 10.1007/s00421-018-3967-z
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring stiffness pattern during contraction in healthy individuals: analysis by ultrasound-based shear wave elastography

Abstract: The stiffness distribution among the hamstring muscles during submaximal isometric contractions is heterogeneous, but symmetric between limbs, and changes depending on the contraction intensity. Shear wave elastography is a reliable tool to assess the stiffness of hamstring muscles during contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 45 publications
(57 reference statements)
2
42
0
Order By: Relevance
“…4). 34 Several studies showed greater stiffness of contracted muscle compared with the relaxed muscle (►Fig. 5).…”
Section: Musclementioning
confidence: 99%
See 1 more Smart Citation
“…4). 34 Several studies showed greater stiffness of contracted muscle compared with the relaxed muscle (►Fig. 5).…”
Section: Musclementioning
confidence: 99%
“…69 Different transducer positioning has been used across studies (transverse versus longitudinal position). 34 The shear waves propagate faster in contracted tendons and muscles and along the long axis of tendons. The transducer must be oriented longitudinally to the muscle fibers to achieve accurate and reliable SWE measurements.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…force) and strain (deformation). A growing body of literature demonstrates the utility of SWE method for assessing muscle stiffness [3][4][5][6][7][8][9][10][11][12]. The shear modulus obtained with SWE has been validated for assessing muscle stiffnes, by using isolated meat speciments and comparing it to direct mechanical stiffness measures.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the SWE for assessing muscle stiffness has been shown to be good or excellent for several muscle groups, including lower limb [5,11,12,14], trunk [4,10] and upper limb muscles [3,[6][7][8][9]. It has been suggested that SWE could also be used to monitor muscle activity [9,12,15,16]. Namely, strong withinindividual associations were shown between shear modulus values and muscle activity or muscle force [9,12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation